Frequency Of Fetal Congenital Abdominal Anomalies Diagnosed On Ultrasound In Gujrat Pakistan: A Cross-sectional Study - Hasan, Atika; Ahmad Naeem, Muhammad; Ali, Abid; Arshad, Nosheen; Naqi Abbas, Syed; Mumtaz, Hassan (Medical Science Journal for Advance Research, 2022)
Introduction: A congenital abnormality is referred to as a congenital illness or deformity. In the first four weeks of life, 276,000 newborns die from congenital impairments, giving birth to a total of around 3 million fetuses and babies; these fetuses and infants are affected by abdominal fetal deformities. Each demographic has a different prevalence of birth defects. Using standard ultrasonography, we set out to find out how often it is to see congenital fetal abdominal abnormalities in Gujrat District of Pakistan. Methods: From January 2022 to June 2022, researchers will conduct cross-sectional study at the Azeem Diagnostic Center Gujrat. 397 This research included pregnant women in the first, second, and third trimesters. Statistical analysis of prenatal ultrasound findings was carried out via the use of a structured questionnaire. A p-value of less than 0.05 was considered significant when using the Chi-square test to look for a relationship. Odds Ratio was used to calculate illness risk. Results: Twenty separate pregnant women who had ultrasounds had fetal congenital impairments discovered. Patients with Atresia or Renal Agenesis are nine times more likely to have an Omphalocele than those without (odds ratio = 0.994, 95 percent confidence range = 0.986-1.002). Conclusion: It is a noninvasive imaging technique that is incredibly sensitive and accurate while also being quite affordable in the hands of a skilled professional. At least during the second trimester, obstetricians should encourage their patients to get regular ultrasounds.